Perilaku Pemberian Makan Orang Tua Prediktor Negatif Kejadian Stunting Anak Usia 24-59 Bulan - Dewi Maghfirotun; Prastiwi Putri Basuki; Yuli Ernawati (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2021)
Poor nutritional condition is one of the causes of stunting. Parental feeding behavior plays a role in improving children's nutritional status. The purpose of this research was to discover the correlation between parental feeding behavior and the incident of stunting among children aged 24-59 months at Sidoluhur Village Working Area of the Godean 1 Sleman Community Health Center. The research methods used an observational analytic design with a cross-sectional study. The respondents have conducted 72 parents with children aged 24-59 months who fit the inclusion and exclusion criteria. Parental feeding behavior was assessed using the Parental Feeding Behavior Questionnaire which consists of 38 questions. The incidence of stunting was assessed by height indicator according to age (height/aged) were compared with z-score. Data were analyzed using Sommer's d correlation. The result of the study indicates that parental feeding behavior is not associated with the incidence of stunted (p = 0,639; r = -0,073). The average of parental feeding behavior mostly with sufficient category (59,7%). The incidence of stunting showed that 1 child (1,4%) with stunting and 8 children (11,1%) with severe stunting.